Предмет: Алгебра,
автор: Хульминация
(-c-3) (c+1)
(11a-4)(3-2a)
(x-t)(x в квадрате+2xt-3t в квадрате)
Ответы
Автор ответа:
0
(-c - 3)(c + 1) = -с² - с - 3с - 3 = -с² - 4с - 3
(11a - 4)(3 - 2a) = 33а - 22а² - 12 + 8а = -22а² + 41а - 12
(x - t)(x² + 2xt - 3t²) = х³ + 2х²t - 3xt² - x²t - 2xt² + 3t³ = х³ + х²t - 5xt² + 3t³
(11a - 4)(3 - 2a) = 33а - 22а² - 12 + 8а = -22а² + 41а - 12
(x - t)(x² + 2xt - 3t²) = х³ + 2х²t - 3xt² - x²t - 2xt² + 3t³ = х³ + х²t - 5xt² + 3t³
Похожие вопросы
Предмет: Алгебра,
автор: alikaponjikponjikov
Предмет: Русский язык,
автор: janastaroi2018
Предмет: Алгебра,
автор: hellokittihi0
Предмет: Химия,
автор: Марьяна1234
Предмет: Литература,
автор: ipsautcina